Microstructure transition and selection of Al2O3/Er3Al5O12/ZrO2 ternary eutectic ceramics from micronscale to nanoscale: The effect of rapid solidification. Issue 2 (1st February 2018) - Ren, Q.; Su, H.J.; Zhang, J.; Fan, G.R.; Lu, Z.; Ma, W.D.; Wang, E.Y.; Liu, H.F.; Ren, J.F.; Liu, L.
Abstract: Microstructure transition and selection of Al2 O3 /Er3 Al5 O12 /ZrO2 ternary eutectic ceramics with minimal eutectic spacing of 50 nm are studied by laser zone melting under rapid solidification rate. When the eutectic spacings are in micronscale, the 'Chinese script' structure is the main microstructure. As increasing the solidification rate (≥ 50 µm/s), the eutectic colony structure is obviously formed. The irregular-regular structural transition and coexistence are produced around eutectic spacing of 100–200 nm. The mechanism of irregular/regular eutectic structure transition and coexistence is revealed by considering the relative kinetic undercooling of each phase. In addition, the strong formation tendency of amorphous/nano-eutectic structure is observed at the surface of as-solidified ceramic drops by rapid liquid-metal quenching.